2013
DOI: 10.3892/br.2013.70
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimuli improve osteogenic differentiation mediated by aniline pentamer and PLGA nanocomposites

Abstract: Electrical stimulation may improve the proliferation of animal cells. In the present study, osteoblasts were cultured on electroactive aniline pentamer (AP)/poly(lactic-co-glycolic acid) (PLGA) copolymer composites, on which electric pulse was imposed. The combination of polymer and electric pulse enhanced the osteogenic differentiation of the osteoblasts, characterized by the upregulated expression of bone morphogenetic protein (BMP)-2, collagen I and osteonectin and the phosphorylation of Samd4, in contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In fact, some studies have shown the possibility of tissue regeneration with modest electrical stimulation resulting in DNA synthesis and proliferation [202]. A recent study by Cao et al evaluated the effects of electrical stimulation via electrically conductive aniline pentamer-PLGA composites on bone cells [203]. The study showed, composites containing a minor portion of aniline pentamer (5% by wt) elicited a 50% increase in cell viability at earlier time points (1-day) and a slightly lower (30%) cell viability at longer time points (7-days).…”
Section: Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some studies have shown the possibility of tissue regeneration with modest electrical stimulation resulting in DNA synthesis and proliferation [202]. A recent study by Cao et al evaluated the effects of electrical stimulation via electrically conductive aniline pentamer-PLGA composites on bone cells [203]. The study showed, composites containing a minor portion of aniline pentamer (5% by wt) elicited a 50% increase in cell viability at earlier time points (1-day) and a slightly lower (30%) cell viability at longer time points (7-days).…”
Section: Bone Regenerationmentioning
confidence: 99%
“…The study showed, composites containing a minor portion of aniline pentamer (5% by wt) elicited a 50% increase in cell viability at earlier time points (1-day) and a slightly lower (30%) cell viability at longer time points (7-days). In addition to cell viability, they further showed that BMP-2, collagen-I, and osteonectin expression were upregulated at all time points in composites containing aniline pentamers, thereby demonstrating the usefulness of electrical stimulation on osteogenesis [203]. Similarly to this study, Bagchi et al studied the electrical, mechanical, and chemical properties of three perovskite ceramic filled (calcium-, barium-, and strontium titanate) aliphatic polyester based composites on their capability to induce osteogenesis.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…[4,5] However, the electrically nonconductive nature of hydrogels impedes its use for excitable cells such as neural, skeletal and cardiac muscle, and bone cells. [6,7] To extend the utility of hydrogels, conducting 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 elements like metallic nanoparticles [8][9][10][11][12][13][14] and inherently conductive polymers (IHPs) [6,[15][16][17][18][19] have been incorporated within hydrogel matrices in order to add conductive properties to the 3D microenvironments.…”
Section: Introductionmentioning
confidence: 99%
“…2). 9,46 Each well experienced an electrical signal with a 2 V voltage and 100 Hz frequency for 2 h/day for 7 and 14 days. The conductive scaffolds were placed on the top of the electrodes and in contact with them.…”
Section: Electrical Stimulationmentioning
confidence: 99%